USING THE VOX-POP METHOD IN TEACHING A FOREIGN LANGUAGE TO YOUNG LEARNERS - Rustamov, Ilxom; Ataboyev Isroiljon Mirza o`g`li (Журнал иностранных языков и лингвистики, 2023)
One of the most important methods will be the vox pop method, which can give the learners a chance to be in a real situation and improve their intelligence. In the 21st century, every teacher tries to use modern and effective methods in their teaching process and encourage learners to learn the language well in real-life situations. For this purpose, we have many methods to educate learners in class or outside of class.